Efficacy and safety of mogamulizumab by patient baseline blood tumour burden: a post hoc analysis of the MAVORIC trial. (20th August 2021) - Cowan, R.A.; Scarisbrick, J.J.; Zinzani, P.L.; Nicolay, J.P.; Sokol, L.; Pinter‐Brown, L.; Quaglino, P.; Iversen, L.; Dummer, R.; Musiek, A.; Foss, F.; Ito, T.; et al.
Abstract: Background: Mogamulizumab was compared with vorinostat in the phase 3 MAVORIC trial (NCT01728805) in 372 patients with relapsed/refractory mycosis fungoides (MF) or Sézary syndrome (SS) who had failed ≥1 prior systemic therapy. Mogamulizumab significantly prolonged progression‐free survival (PFS), with a superior objective response rate (ORR) vs. vorinostat. Objectives: This post hoc analysis was performed to evaluate the effect of baseline blood tumour burden on patient response to mogamulizumab. Methods: PFS, ORR, time to next treatment (TTNT), skin response (modified Severity‐Weighted Assessment Tool [mSWAT]) and safety were assessed in patients stratified by blood classification (B0 [ n = 126], B1 [ n = 62], or B2 [ n = 184], indicating increasing blood involvement). Results: Investigator‐assessed PFS was longer for mogamulizumab versus vorinostat across all blood classes, significantly so for B1 and B2 patients. ORR was higher with mogamulizumab than with vorinostat in all blood classification groups and more markedly so with escalating B class (B0: 15.6% vs. 6.5%, P = 0.0549; B1: 25.8% vs. 6.5%, P = 0.2758; B2: 37.4% vs. 3.2%, P < 0.0001). TTNT was significantly longer for patients treated with mogamulizumab versus vorinostat with B1 (12.63 vs. 3.07 months; HR 0.32 [95% CI 0.16–0.67]; P = 0.0018) and B2 (13.07 vs. 3.53 months; HR 0.30 [95% CI 0.21–0.43]; P < 0.0001) blood involvement. In the mogamulizumab arm, 81 patients (43.5%) had ≥50% change in the mSWAT vs. 41 patients (22.0%) with vorinostat; mSWAT improvements with mogamulizumab occurred most often in B1 and B2 patients. Rapid, sustained reductions were seen in CD4 + CD26 ‐ cell counts and CD4:CD8 ratios in mogamulizumab patients for all B classes. Treatment‐emergent adverse events were less frequent overall with mogamulizumab and similar in frequency regardless of B class. Conclusions: This post hoc analysis indicates greater clinical benefit with mogamulizumab vs. vorinostat in patients with MF and SS classified as having B1 and B2 blood involvement.